Solar light mediated anthracene abatement in aerated aqueous media using a thermoplastic nanocomposite photocatalyst. (September 2022) - Vento, Fabiana; Nicosia, Angelo; Mezzina, Lidia; Rodríguez-Muñiz, Gemma M.; Miranda, Miguel A.; Mineo, Placido G.; De Guidi, Guido
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are the most widespread xenobiotic pollutants in water and their abatement usually involves expensive and energy-consuming treatments. In this work, anthracene (AN) was selected as the recalcitrant model of PAHs and its solar light-stimulated heterogeneous photocatalytic abatement in aerated aqueous media was investigated using a new TiO2 derived thermoplastic nanocomposite in thin film form. The results were also compared with the benchmark TiO2 photocatalyst in slurry form. Finally, the possible contribution of reactive intermediates such as hydroxyl radical, AN radical cation and singlet oxygen, was investigated by using a hydroxyl radical trap and laser flash photolysis. Based on the obtained results, a feasible mechanism for AN photodegradation, which involves hydroxyl radical as the key oxidizing species is proposed. Graphical abstract: Image 1 Highlights: Polycyclic aromatic hydrocarbons remediation through solar photocatalysis. A TiO2 -based photocatalytic nanocomposite was employed in anthracene abatement. The photodegradation by-products were identified with UV–Vis and HPLC analyses. The abatement efficiency of the nanocomposite was higher than that of TiO2 powder. The data suggest hydroxyl radical as key species of the photodegradation mechanism.